In vitro evaluation of the antifungal activity of Heliopsis longipes extract in strains of Sclerotium cepivorum and Sclerotinia sclerotiorum - Delgado Ortiz, Juan Carlos; Ochoa Fuentes, Yisa María; Beltrán Beache, Mariana; Cerna Chávez, Ernesto (Revista Mexicana de Ciencias Agrícolas, 2018)
White rot and soft rot caused by Sclerotium cepivorum and Sclerotinia sclerotiorum are the main cause of losses in garlic and lettuce crops, making their control difficult due to the production of sclerotia. An environmentally friendly alternative to disease control is the use of plant extracts; like Heliopsis longipes, which has the capacity to produce alcamidas like afinina, which are responsible for its effect as an insecticide and bactericide, it is worth mentioning that this compound is found in greater proportion in the roots of the plant. Therefore, the biological material was collected in Guanajuato in 2013, from which the fungus was isolated and in which the antifungal activity of the extract was evaluated and the viability of the sclerotia of Sclerotium cepivorum and Sclerotinia sclerotiorum was verified. through the technique of poisoned medium. Obtaining percentages of inhibition higher than 75% for the strains of Sclerotium cepivorum, while for Sclerotinia sclerotiorum less than 40%. In addition to showing statistically significant reduction in the production of sclerotia and only affect the vigor of growth in one of the strains evaluated. Therefore, the extract showed to be effective in the control of the parameters evaluated.
Keywords: Heliopsis longipes; Sclerotium cepivorum; Sclerotinia sclerotiorum; viability of sclerotia